2020
DOI: 10.3389/fpsyt.2020.588968
|View full text |Cite
|
Sign up to set email alerts
|

How Resilience Promotes Mental Health of Patients With DSM-5 Substance Use Disorder? The Mediation Roles of Positive Affect, Self-Esteem, and Perceived Social Support

Abstract: Objectives: The existing studies found that resilience is a salient trait that can significantly affect people's psychological well-being with substance use disorders (SUDs). However, few studies examined how the mechanisms are connected between resilience and mental health among patients with Diagnostic and Statistical Manual of Mental Disorders—fifth edition SUD. This study investigated the mediation effects of positive affect, perceived social support, and self-esteem on the effect of resilience on perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 106 publications
(130 reference statements)
4
24
0
1
Order By: Relevance
“…Distress directly related to COVID-19, as well as the unintended social and economic consequences of lockdowns contributed to increased patterns of substance misuse, along with alcohol- and drug-related overdoses ( Centers for Disease Control and Prevention, 2020a , Czeisler, 2020 , Mougharbel et al, 2021 , Nguyen and Buxton, 2021 ). This was foreseen by many, as stress has long been linked to substance abuse and risk of relapse ( Yang et al, 2020 ). Alarmingly, a prevailing concern is that the pandemic will have long-lasting impacts on mental and behavioral health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distress directly related to COVID-19, as well as the unintended social and economic consequences of lockdowns contributed to increased patterns of substance misuse, along with alcohol- and drug-related overdoses ( Centers for Disease Control and Prevention, 2020a , Czeisler, 2020 , Mougharbel et al, 2021 , Nguyen and Buxton, 2021 ). This was foreseen by many, as stress has long been linked to substance abuse and risk of relapse ( Yang et al, 2020 ). Alarmingly, a prevailing concern is that the pandemic will have long-lasting impacts on mental and behavioral health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of PLWH in Argentina showed that resilience mitigated the impact of economic disruptions on mental health during the COVID-19 pandemic ( Ballivian et al, 2020 ). Others have also shown that higher levels of resilience are associated with less perceived stress and higher life satisfaction in PWUD, two critical factors involved in SUDs ( Yang et al, 2020 ). These results support the notion that psychological resilience serves as a buffer against poor mental health that may directly and indirectly protect from substance misuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study exemplified that better performance in family functioning indicated greater resilience and predicted better mental health in hemodialysis patients (Kukihara et al, 2020). Resilience and life satisfaction are partially mediated by perceived social support in substance use disorder (Yang et al, 2020). Higher resilience is associated with better psychosocial functioning, which has been investigated in clinically stable BD outpatients (Mizuno et al, 2016).…”
Section: Introductionmentioning
confidence: 57%
“…Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs. Consequently, specific components of early recovery social networks, such as network size (133,139,145), quality (146), and density (138) have proven to be important factors in recovery outcomes. Strong associations have been found between ongoing contact with substance users and continued substance use (147).…”
Section: Discussionmentioning
confidence: 99%